A Study on Impact of Conservation Community Network on Environment and Receive Household: The Case study of Pakkading District, Bolikhamsai Province - Seehalad, Bounma (International Journal of Multidisciplinary in Management and Tourism, 2020)
This final project is to study on impact of Conservation Community Network on Environment and Receive household in Pakkading district, Bolikhamsai province. The purpose of this study is to investigate the impact of CCN by comparing between Village have CCN and don’t have CCN. We used the Logistic Regression, and to examine the impact of Conservation Community Network (CCN) on Receive household, and the number of samples equal to 295 households. The result of model analysis: the dependent variable which effect to change of environment are: the village have the CCN positive impact of environment, gender and household size negative impact to the environment. The dependent variable which effect to receive households are: the village have CCN, gender, land, loan size positive impact to receive households, occupation and number of going to forest negative impact to receive households.